Analisis Pengaruh Kualitas Layanan terhadap Kepuasan Pelanggan dan Loyalitas Pelanggan E-Commerce Shopee - Firdaus, Rizal Awaluddin; Astuti, Budi (Jurnal Informatika Ekonomi Bisnis, 2024)
This study explores the impact of service quality on customer satisfaction and loyalty on the Shopee e-commerce platform, using Means-End Chain Theory (MEC) as the theoretical foundation. The research employs a quantitative method, with primary data collected through an online questionnaire. Conducted in Yogyakarta, the study involves 260 respondents selected using purposive sampling, targeting users of the Shopee app or website. The data is analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study measures five dimensions of service quality: efficiency, fulfillment, privacy & security, responsiveness, and accessibility. The results show that efficiency, accessibility, privacy & security, and responsiveness have a positive and significant impact on customer satisfaction. In contrast, fulfillment does not significantly affect satisfaction. For customer loyalty, efficiency and responsiveness have a significant impact, while accessibility, privacy & security, and fulfillment do not. These findings provide valuable insights for Shopee to enhance specific aspects of service quality to improve customer satisfaction and loyalty.